Implications of COVID-19 and Lockdown on Internet Addiction Among Adolescents: Data From a Developing Country - Siste, Kristiana; Hanafi, Enjeline; Sen, Lee Thung; Murtani, Belinda Julivia; Christian, Hans; Limawan, Albert Prabowo; Siswidiani, Levina Putri; Adrian, (Frontiers in Psychiatry, 2021)
Introduction: Physical distancing policy during COVID-19 pandemic requires adolescents to spend most of their time at home, thus increasing Internet use duration. Limited social interaction with their peers may lead to loneliness and an increased risk of mental health among adolescents. This study aimed to assess the prevalence of IA among adolescents and analyze the influence of psychosocial factors toward the heightened risk of IA during the COVID-19 pandemic. Methods: An online survey comprising sociodemographic questionnaire, Internet Addiction Diagnostic Questionnaire (KDAI), Strengths and Difficulties Questionnaire (SDQ) and Pittsburgh Sleep Quality Index (PSQI), was distributed. Overall, a total of 2,932 adolescents (mean age 17.38±2.24 years old and 78.7% females), originating from 33 of 34 provinces in Indonesia, completed the survey. Results: The point-prevalence of IA among Indonesian adolescents during the COVID-19 outbreak was 19.3%. Increased Internet use duration, internalization, externalization, low prosocial behavior, and sleep disturbances were found as risk factors of IA, either directly or as mediating variables. Physical distancing, large-scale social restriction (PSBB), and health status were not correlated to IA. Discussion: Physical distancing was not established as a risk of IA. This could be due to other psychological factors such as internalization, externalization, prosocial, and sleep problems that had correlations to IA occurrence among adolescents in the COVID-19 pandemic. Sleep impairment might have resulted from the emotional and behavioral issues or directly contributed to IA development. Conclusion: The present study found the prevalence of IA among Indonesian adolescents to be higher than the adult during the COVID-19 pandemic. Several psychological measures were indicated to increase the risk of IA, while physical distancing did not elevate the risk. Thus, remote schooling is preferable in Indonesia along with proper parents' supervision to minimize internet use for entertainment purposes.